Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

How can we prove that 4x+2(x+3)=8x+6

Sagot :

This equation is not correct. Because,

[tex]4x+2(x+3)\quad =\quad 4x+2\cdot x+2\cdot 3=4x+2x+6=\quad 6x+6[/tex]

And

[tex]6x+6\quad \neq \quad 8x+6[/tex]

The only possible, solution for this equation would be, x=0.  Because,

for x=0 :

[tex]4\cdot 0+2\cdot (0+3)=8\cdot 0+6=\quad 0+2\cdot 0+2\cdot 3=0+6\quad \Longrightarrow \quad 6=6[/tex]
4x+2(x+3)=8x+6
4x+2x+6=8x+6
4x-8x=6-6
-4x=0
x=0
HOPE I HELPED!!!